Functional business valuation – The theoretical foundation of argumentation value and its underlying function - Matschke, Manfred Jürgen; Brösel, Gerrit; Thielmann, Patrick (Managerial Economics, 2021)
Functional business valuation is the prevailing doctrine in the theoretically well-founded German-language literature, because the value of a company is primarily dependent on the purpose (function) of the valuation. This paper deals with one of the three main functions of business valuation: the argumentation function. This is where the argumentation value of the business is determined. The argumentation function is the function that has been the least theoretically developed and accepted to date, but is probably the most commonly used one in the real world. This article shows for the first time in the English-language literature the core ideas of the theoretical foundation of this function.